The Impact of Fiscal Decentralization on Economic Growth in Central and Eastern Europe - Korotun, Volodymyr; Kaneva, Tetiana; Drepin, Anton; Levaieva, Liudmyla; Kucherenko, Svitlana (European Journal of Sustainable Development, 2020)
In this research, we evaluated the impact of fiscal decentralization on GDP per capita growth. Using the unbalanced panel data, the authors assessed the interconnections between fiscal decentralization – considering its expenditure and revenue aspects as well as tax autonomy – and economic growth for Central and Eastern European countries from 1995 to 2018. In the examined states, the expenditure decentralization exceeded the revenue one. We found out that revenue decentralization and tax autonomy adversely affected economic growth. But expenditure decentralization associated with a positive GDP growth rate. In this paper, we also explored the peculiarities of fiscal decentralization reform. Structural transformations radically reduced the size of the public sector in Central and Eastern Europe, which had a positive effect on the economy. The vital components of local budgets tax revenues are personal income tax and the property taxes. The most effective mechanism for the property tax base’s determination arises from the value of the real estate or land. Keywords: fiscal policy, fiscal decentralization, tax autonomy, property taxes, economic growth